Catecholaminergic gene polymorphisms are associated with GI symptoms and morphological brain changes in irritable bowel syndrome - Orand, Alexa; Gupta, Arpana; Shih, Wendy; Presson, Angela P.; Hammer, Christian; Niesler, Beate; Heendeniya, Nuwanthi; Mayer, Emeran A.; Chang, Lin (PLOS ONE, 2015)
Background Genetic and environmental factors contribute to the pathophysiology of irritable bowel syndrome (IBS). In particular, early adverse life events (EALs) and the catecholaminergic system have been implicated. Aims To investigate whether catecholaminergic SNPs with or without interacting with EALs are associated with: 1) a diagnosis of IBS, 2) IBS symptoms and 3) morphological alterations in brain regions associated with somatosensory, viscerosensory, and interoceptive processes. Methods In 277 IBS and 382 healthy control subjects (HCs), 11 SNPs in genes of the catecholaminergic signaling pathway were genotyped. A subset (121 IBS, 209 HCs) underwent structural brain imaging (magnetic resonance imaging [MRI]). Logistic and linear regressions evaluated each SNP separately and their interactions with EALs in predicting IBS and GI symptom severity, respectively. General linear models determined grey matter (GM) alterations from the SNPs and EALs that were predictive of IBS. Results 1) Diagnosis: There were no statistically significant associations between the SNPs and IBS status with or without the interaction with EAL after adjusting for multiple comparisons. 2) Symptoms: GI symptom severity was associated with ADRA1D rs1556832 (P = 0.010). 3) Brain morphometry: In IBS, the homozygous genotype of the major ADRA1D allele was associated with GM increases in somatosensory regions (FDR q = 0.022), left precentral gyrus (q = 0.045), and right hippocampus (q = 0.009). In individuals with increasing sexual abuse scores, the ADRAβ2 SNP was associated with GM changes in the left posterior insula (q = 0.004) and left putamen volume (q = 0.029). Conclusion In IBS, catecholaminergic SNPs are associated with symptom severity and morphological changes in brain regions concerned with sensory processing and modulation and affect regulation. Thus, certain adrenergic receptor genes may facilitate or worsen IBS symptoms.
Gesehen am 24.06.2020